2020
DOI: 10.1002/esp.4981
|View full text |Cite
|
Sign up to set email alerts
|

Runoff‐generated debris flows: Observation of initiation conditions and erosion–deposition dynamics along the channel at Cancia (eastern Italian Alps)

Abstract: In the Dolomitic region, abundant coarse hillslope sediment is commonly found at the toe of rocky cliffs. Ephemeral channels originate where lower permeability bedrock surfaces concentrate surface runoff. Debris flows initiate along such channels following intense rainfall and determine the progressive erosion and deepening of the channels. Sediment recharge mechanisms include rock fall, dry ravel processes and channel-bank failures. Here we document debris flow activity that took place in an active debris flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 61 publications
(125 reference statements)
3
64
2
Order By: Relevance
“…14c) and influx of debris flow material from the slope. Though the present study noted the influence of channel morphology on the debris flow characteristics, other studies have observed the changes in channel morphology caused by the debris flows (Remaître et al, 2005;Simoni et al 2020).…”
Section: Discussioncontrasting
confidence: 59%
“…14c) and influx of debris flow material from the slope. Though the present study noted the influence of channel morphology on the debris flow characteristics, other studies have observed the changes in channel morphology caused by the debris flows (Remaître et al, 2005;Simoni et al 2020).…”
Section: Discussioncontrasting
confidence: 59%
“…(2020); Simoni et al. (2020) for 20 of the 41 DFs (Table 3). Therefore, for the sake of homogeneity, we used the entire precipitation of the event in all the cases.…”
Section: Study Sitementioning
confidence: 96%
“…For identifying the rainfall beginning time, we applied the definition of burst used by Coe et al (2008). The timing of occurrence is known by the monitoring stations of Bernard, Berti et al (2019); Berti et al (2020); Simoni et al (2020) for 20 of the 41 DFs (Table 3). Therefore, for the sake of homogeneity, we used the entire precipitation of the event in all the cases.…”
Section: Monitoring Network and Rainfall Datamentioning
confidence: 99%
“…The estimation of the sediment volume mobilized by a debris ow can be carried out by the differences of pre-and post-events DEMs (Simoni et al, 2020). But the DEMs before and after a debris ow event is di cult to be obtained timely (Mohammad and Ali, 2017;Hassan and Banihabib 2016;Schürch et al 2011).…”
Section: Estimating the Annual Volume Of Debris Owsmentioning
confidence: 99%
“…Debris ows are mixtures of soil, sand, stones, and water that transport large amounts of sediment downstream, which can cause serious damage and economic losses (Lyu et al, 2020). Debris ows often start from landslides and channel bed failures (Gabet and Mudd, 2006;Gregoretti and Dalla Fontana, 2008;Simoni et al, 2020), moraine lake outbursts (McCoy et al, 2012), and glacial melting (Lyu, 2017b).…”
Section: Introductionmentioning
confidence: 99%